Morphology, anatomy and molecular characteristics of Blechnaceae ferns from Peninsular Malaysia - Mat Hussin, Nur Syamim Syahirah (2014)
The arguments and unclear status upon Blechnaceae taxonomic classification which considered as monophyletic by several authors but showing different results to others has growing interest to study this family. Blechnaceae from Peninsular Malaysia which represented by four genera; Blechnum, Woodwardia, Brainea and Stenochlaena were studied. These ferns were distributed and collected from three different states namely Pahang, Johor and Selangor. The taxonomic placement of this ferns at ordinal and familial was categorized differently among previous taxonomist. This may confound present access and brought difficulty to identify the plants. Furthermore, molecular data previously has also resulted with two-differently species relation among Blechnaceae; (1) monophyletic, and (2) not monophyletic. These findings have brought intense interest to study ferns of Blechnaceae with objectives to document the macro morphological characters including rhizome, frond architecture, venation and scales. Each character was observed and identified upon similarities and differences with aid of magnification. The sectioned of stipe and rachis from fresh specimens were done to study vascular bundle arrangement. Meanwhile, to classify this family using molecular approaches, chloroplast coding and non-coding regions of rbcL, atpB and trnH-psbA were amplified using Polymerase Chain Reaction (PCR) and the sequences were analyzed to indicate species relatedness. All data were compiled using NCSS9 Statistical Software and Graphic Analysis and further analyzed using the Unweighted-Pair Group method. The results of the study showed Blechnaceae is not monophyletic. Blechnum was found to be clustered into two clades, while Brainea and Woodwardia were treated as the ancestors to the family. Stenochlaena was found closely related to B. indicum, whereas a new species of Blechnum sp. was relatively close and much resembled B. orientale. The result obtained from clustering analysis was supported by the Maximum Parsimony analysis using the nucleotide sequences from rbcL, atpB and trnH-psbA. RbcL and trnH-psbA were found as two reliable markers in this study due to its parallel hypothesis in inferring the species relatedness. However, atpB sequences were too short and could be unreliable to resolve the species relationship. The classification by clustering analyses using macro and micro morphological characters were unparallel with the molecular finding. All species were found as not monophyletic and but able to be distinguished separately. Each species had their own characters but some of them shared with overly similarly characters. However, the data from this study could be use for future references when conducting research of ferns from Peninsular Malaysia.